Educación y mercado laboral: Revisión de la literatura y algunos hechos para la Argentina - Jorge A. Paz (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2005)
– This work studies the relationship between education and labor market performance, first by making a review of the literature on the subject, and then by examining certain stylized facts. For the empirical evaluation, education is analysed through the educational attainment reached by economic agents and the labor market by certain results: remunerations, probabilities to participate, to be employed or unemployed. The issue of the probability to access better jobs is also approached. Therefore, education is here discussed as an input, and labor market results, as an output.
Keywords: I20; J24; 330; Bildung; Humankapital; Arbeitsmarkt; Bildungsertrag; Argentinien